Scale For Measuring Arabic Speaking Skills In Early Children's Education - Mustapha Qureshi; Dinnah Mahdiyyah; Yassine Mohamed; Mounika Ardchir (Journal International of Lingua and Technology, 2022)
Learning Arabic speaking skills depends on the teacher's teaching to his students by choosing learning media according to the needs and goals of a teacher to realize Arabic speaking skills to his students. The purpose of this research is the implementation of the learning activities of hand puppet media to improve the speaking skills of Sungai Tarab State Islamic Elementary students. Then, hand puppet media can improve the speaking skills of Sungai Tarab State Islamic Elementary students. This study uses two rounds of classroom action research. Each round consists of four stages: planning, implementation, observation and reflection. The research population was all students of Islamic Elementary School Sungai Tarab, while the sample was class Three Islamic Elementary School Sungai Tarab, totaling 35 students. Data collection techniques using interview, observation and documentation methods. At the same time, the analysis technique used in analyzing is data reduction, data presentation and conclusion drawing. The results of this study indicate that the use of hand puppet media in learning Arabic can improve the ability to speak Arabic for the third-grade students of Islamic Elementary School Sungai Tarab in learning activities.